Lama Ekstraksi Daun Rhoeo discolor Dengan Berbagai Variasi Pelarut Sebagai Indikator Asam Basa Alami - Novitasari, Shinta Putri; , Dra. Aminah Asngad, M.Si (2017)
The acid-base indicator is the required material in the laboratory of the substance classification material. The leaf of Rhoeo discolor can be used as natural indicator acid base because they contain anthocyanin. The aim of this research was to know the color change of natural acid indicator paper through the long immersion of Rhoeo discolor leaf with variation of solvent. This research is eksperimental method used by Completely Randomized Design (CRD), with two treatment factors that is length immersion of Rhoeo discolor's leaf and variation of Solvent. The results showed differences color paper on Rhoeo discolor leaf submersion until 23 hours, 24 hours, and 25 hours. Type of 95% ethanol solvent paper is green, 95% ethanol + 3% citric acid is pink, and 95% ethanol + CH3COOH is orange vinegar. Indicator paper with 95% ethanol solvent + 3% citric acid after immersion with strong acid or weak pink acid, strong lemon green base and weak green base chartreuse.